2016
DOI: 10.5505/tjtes.2016.27895
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ranson score and red cell distribution width (RDW) in acute pancreatitis

Abstract: BACKGROUND: Ranson's criteria are widely used to evaluate severity of acute pancreatitis (AP). Red blood cell distribution width (RDW) has been demonstrated to be useful marker to predict mortality in these patients. The aim of the present study was to investigate correlation between Ranson score and RDW in patients with AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Apart from the CVDs discussed above, RDW has a distinct impact on various pathophysiological mechanisms in diseases ranging from MI to dementia. The predictive roles of RDW in other diseases including acute pancreatitis, diabetic nephropathy, Hodgkin lymphoma, and upper gastrointestinal hemorrhage have also been proposed [ 121 , 122 , 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the CVDs discussed above, RDW has a distinct impact on various pathophysiological mechanisms in diseases ranging from MI to dementia. The predictive roles of RDW in other diseases including acute pancreatitis, diabetic nephropathy, Hodgkin lymphoma, and upper gastrointestinal hemorrhage have also been proposed [ 121 , 122 , 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some serum pro- and anti-inflammatory markers have been proved to be associated with AP severity, such as interleukin-6, interlekin-8, interleukin-10 and tumor necrosis factor alpha; and serum procalcitonin, a reliable marker of infection/sepsis and useful for predicting infected necrosis in AP. However, the main handicaps of these markers are the fact that they are not routinely used and associated with significant additional costs [ 2 , 6 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…[3] There is no consensus on markers established for di-predicting the severity of the disease. [7,8] In addition, many clinical studies have reported that easily accessible markers, such as the neutrophil/lymphocyte ratio, the platelet/lymphocyte ratio, the red cell distribution width (RDW), and the level of procalcitonin can be helpful in predicting severity and prognosis of pancreatitis to different degrees. There are also a few studies in the literature reporting that the CRP/albumin ratio can be used in this respect.…”
Section: Introductionmentioning
confidence: 99%